Massachusetts State House draped in black bunting to mourn President William McKinley, September 1901 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of Bulfinch's State House from Beacon Street. The facade of the building is draped in black bunting and American flags to mourn the assassination of President William McKinley. A photograph of President McKinley is located between the center two columns on the second level of the State House. Statues of Daniel Webster and Horace Mann flank both sides of the main steps on the south lawn. Three women descend the main steps, while a fourth woman walks along Beacon Street and looks toward the State House. President William McKinley was shot on September 6, 1901, by anarchist Leon Czolgosz. The president died on September 14, 1901. Donated by Robert Severy. 4 13/16 x 3 1/2, 5 1/2 x 4 7/16 overall Photographs